1991
DOI: 10.1051/agro:19910506
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pea seed-borne mosaic virus virion and pinwheel inclusion body proteins in leaf and seed tissues of pea (Pisum sativum L) by immunogold labelling

Abstract: Summary — An immunogold labelling procedure was developed to detect pea seed-borne mosaic virus (PSbMV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…This was confirmed by electron microscopy where typical PSbMV-associated structures, including pin-wheel inclusions similar to those seen in leaf mesophyll cells (Wang et al, 1991), were always found in sections of sepal, petal, anther-epidermal tissues and carpel. Virus particles were also observed, most frequently as bundles of particles (Wang et al, 1991). In contrast, none of these structures were seen inside pollen grains or ovules from either cultivar; funicle tissue adjacent to the ovule showed some cells containing PSbMV.…”
Section: Detection Of Psbmv In Floral Tissuessupporting
confidence: 58%
See 1 more Smart Citation
“…This was confirmed by electron microscopy where typical PSbMV-associated structures, including pin-wheel inclusions similar to those seen in leaf mesophyll cells (Wang et al, 1991), were always found in sections of sepal, petal, anther-epidermal tissues and carpel. Virus particles were also observed, most frequently as bundles of particles (Wang et al, 1991). In contrast, none of these structures were seen inside pollen grains or ovules from either cultivar; funicle tissue adjacent to the ovule showed some cells containing PSbMV.…”
Section: Detection Of Psbmv In Floral Tissuessupporting
confidence: 58%
“…Sepal, petal, pollen, anther and carpel samples were collected from infected plants of Progreta and Vedette and assayed for PSbMV using indirect ELISA (Cockbain et al, 1988) or processed for electron microscopy (Wang et al, 1991). Pollen grains from single flowers were washed several times by mild sonication in extraction buffer (20 raM-sodium phosphatebuffered saline, pH 7.4, containing 0.05% v/v Tween 20, 2% polyvinyl pyrrolidone and 0.1% Triton X-100) and centrifugation, and finally ground by mortar and pestle to be used as individual samples in indirect ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…PSbMV has filamentous particles and measures approximately 770 nm in length and 12 nm in width. It can induce the production of inclusion bodies that are pinwheel in shape and aggregate in the mesophyll cells (Hampton et al, 1981;Wang et al, 1991 andMakkouk et al, 1993). PSbMV can infect host range limited to the Fabaceae family such as pea (Pisum sativum), faba bean (Vicia faba), lentil (Lens culinaris), chickpea (Cicer arietinum), and pasture legumes such as alfalfa (Medicago sativa) and vetch (Vicia spp.)…”
Section: Introductionmentioning
confidence: 99%